2021
DOI: 10.1002/cctc.202100977
|View full text |Cite
|
Sign up to set email alerts
|

ZIF‐67 Derived Co/NC Nanoparticles Enable Catalytic Leuckart‐type Reductive Amination of Bio‐based Carbonyls to N‐Formyl Compounds

Abstract: It is of great significance to develop non‐precious metal catalysts with excellent catalytic activity, stability, and acid resistance for biomass valorization. Herein, catalytic amination of biomass carbonyl compounds was achieved via a Leuckart‐type reaction over Co nanoparticles (NPs) embedded N‐doped carbon catalyst, which was prepared by thermolysis of ZIF‐67 precursor at different temperatures in the N2 atmosphere. The Co/NC‐800 catalyst exhibited excellent catalytic activity and recyclability in furfural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…They revealed an average size of 14.7, 10.3, 8.1, and 7.1 nm for Co/NMC-2MeIM (Figure a), Co/NMC-PDCA (Figure b), Co/NMC-BDC-NH 2 (Figure c), and Co/MC-DHTA (Figure d), respectively. Figure e shows the high-resolution TEM (HR-TEM) image of the two adjacent lattice fringes between the rose arrows were ∼0.205 nm, which corresponds to (111) of the face-centered cubic metallic cobalt, while the two adjacent yellow lattice stripes were ∼0.356 nm corresponding to (002) of carbon. The polycrystallinity of cobalt into Co/NMC-2MeIM was confirmed by selected area electron diffraction (SAED), showing the diffraction rings of (002) plane of carbon and (111), (200), (220), and (311) planes of Co 0 (Figure f).…”
Section: Resultsmentioning
confidence: 90%
“…They revealed an average size of 14.7, 10.3, 8.1, and 7.1 nm for Co/NMC-2MeIM (Figure a), Co/NMC-PDCA (Figure b), Co/NMC-BDC-NH 2 (Figure c), and Co/MC-DHTA (Figure d), respectively. Figure e shows the high-resolution TEM (HR-TEM) image of the two adjacent lattice fringes between the rose arrows were ∼0.205 nm, which corresponds to (111) of the face-centered cubic metallic cobalt, while the two adjacent yellow lattice stripes were ∼0.356 nm corresponding to (002) of carbon. The polycrystallinity of cobalt into Co/NMC-2MeIM was confirmed by selected area electron diffraction (SAED), showing the diffraction rings of (002) plane of carbon and (111), (200), (220), and (311) planes of Co 0 (Figure f).…”
Section: Resultsmentioning
confidence: 90%
“…N-doped mesoporous carbon (NMC) has attracted a lot of attention and is used as a catalyst carrier due to its adjustable pore size and functionalization, high surface area, good hydrothermal stability, and electron conduction. Moreover, the replacement of the C atom by a N atom can lower the valence band, increase the chemical stability of the material, and increase the electron density at the Fermi energy level. , According to our previous study, NMC-embedded Ru showed excellent catalytic performance for the hydrogenolysis of LA to GVL, where the weak basicity of the N dopant may promote the adsorption of acidic LA and consequently accelerate the following hydrogenolysis reaction. This inspired us to design and develop a novel NMC-supported Ru multifunctional catalyst for the reductive amination of LA/esters with amines.…”
Section: Introductionmentioning
confidence: 97%
“…The obtained precipitate was dried at 60 °C in a hot air oven over night. [63] 200 mg of CoÀ Co PBA@C was ground in a mortar pestle to get a fine powder. The powder was placed in a crucible boat and heated at 800 °C in the presence of N 2 for 3 h (in a tubular furnace with a heating rate: of 5 °C/min from 35 °C).…”
Section: Methodsmentioning
confidence: 99%